2020
DOI: 10.1021/acsami.0c17479
|View full text |Cite
|
Sign up to set email alerts
|

Kirigami-Inspired Flexible and Stretchable Zinc–Air Battery Based on Metal-Coated Sponge Electrodes

Abstract: The development of efficient and low-cost flexible metal electrodes is significant for flexible rechargeable zinc−air batteries (ZABs). Herein, we reported a new type of flexible metal (zinc and nickel) electrode fabricated via a two-step deposition method on polyurethane sponges (PUS) for flexible ZABs. Compared to conventional electrodes, the metal-coated PUS electrodes exhibited great flexibility, softness, and natural mechanical resilience. In addition, a flexible sandwich-structured ZAB was assembled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…For example, Yao et al (2021) have demonstrated editable and cuttable polyaniline-Zn batteries through different editing programs as a stretchable honeycomblike structure, which could deliver stable electrochemical performance even enduring the tensile strain of up to 400% (Figures 2G,H). In addition, the stretchable Zn-air battery was also demonstrated by the kirigami-cutting strategy, obtaining a 160% stretchable serpentine-shaped battery (Qu et al, 2020) (Figure 2I), where stretchable Zn-air battery can deliver 11.5 Wh L −1 and the performance was stable even subjected to 100% deformation with slight variation of the output voltage compared to the initial state.…”
Section: Structural Designs For Stretchable Zn-based Batteriesmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Yao et al (2021) have demonstrated editable and cuttable polyaniline-Zn batteries through different editing programs as a stretchable honeycomblike structure, which could deliver stable electrochemical performance even enduring the tensile strain of up to 400% (Figures 2G,H). In addition, the stretchable Zn-air battery was also demonstrated by the kirigami-cutting strategy, obtaining a 160% stretchable serpentine-shaped battery (Qu et al, 2020) (Figure 2I), where stretchable Zn-air battery can deliver 11.5 Wh L −1 and the performance was stable even subjected to 100% deformation with slight variation of the output voltage compared to the initial state.…”
Section: Structural Designs For Stretchable Zn-based Batteriesmentioning
confidence: 96%
“…(H) The stable capacity retention under different tensile strain values (reproduced fromYao et al (2021)). (I) Kirigami strategies to realize Zn-air batteries with 100% stretchability to power a fan (reproduced fromQu et al (2020)). (J) The PAM hydrogel electrolyte for mild Zn battery systems with a stretchability over 3,000% (reproduced fromLi et al (2020)).…”
mentioning
confidence: 99%
“…111 The kirigami strategy was also used for fabricating flexible and stretchable supercapacitors, 112,113 transient aqueous batteries, 114 and zinc-air batteries. 115 The origami and kirigami concepts enable FLBs with significant mechanical deformability, including folding, bending, twisting, and stretching, which provided us a design solution for developing FLBs without changing the underlying materials chemistry. However, it should be noted that the existence of predetermined creases and voids also reduced the areal coverage of active materials, decreasing the battery energy densities.…”
Section: Origamimentioning
confidence: 99%
“…The stretchability of sandwich‐type ZABs was studied deeply by several groups. [ 29–31 ] The schematic representation and explored view of a highly stretchable battery array is shown in Figure 1f (left). [ 32 ] Zn foil anodes and Co 3 O 4 ‐modified CC array cathodes were placed face to face on both sides of the solid‐state electrolyte membrane.…”
Section: Flexible Zab Configurationsmentioning
confidence: 99%